Transcriptome Profiling and Identification of the Candidate Genes Involved in Early Ripening in Ziziphus Jujuba - Li, Baiyun; Li, Hui; Xu, Zehua; Guo, Xinnian; Zhou, Tao; Shi, Jiangli (Frontiers in Genetics, 2022)
Early ripening jujube is immensely popular fresh fruit due to higher commercial value as well as rich nutrition. However, little is known about the mechanism of jujube fruit ripening. In this study, the transcriptome profiles were comprehensively analyzed between ‘Lingwu Changzao’ jujube and its early-ripening mutant during the fruit development and maturity. A total of 5376 and 762 differentially expressed genes (DEGs) presented at 80 d and 90 d after flowering of jujube fruit, respectively. Furthermore, 521 common DEGs were identified as candidate genes that might be associated with the fruit early ripening. Our findings demonstrated that in a non-climacteric jujube fruit, abscisic acid (ABA) was more greatly involved in fruit ripening than ethylene. Meanwhile, fruit ripening of the early-ripening mutant was regulated by 8 promotors of DEGs related to glucose and fructose, 7 repressors of DEGs related to brassinosteroid signal transduction, and a series of transcription factor genes (MYB, bHLH and ERF). Additionally, the expression of 20 candidate DEGs were further validated by Real-time PCR during the late fruit mature stage. Collectively, the present study sheds light on the metabolic mechanism of fruit early ripening and provides valuable candidate genes for early-ripening breeding.